INDIKATOR HARGA PANGAN KAITANNYA DENGAN POTENSI PERTANIAN DAN INDUSTRI RUMAHTANGGA DALAM RANGKA MEWUJUDKAN KETAHANAN PANGAN DI KOTA LUBUKLINGGAU (JASEP, 2020)
Food security is a system consist of availablity, distribution, and consumption. Inefficiency of distribution chain, can be harmfull for farmer as price taker if the price maker hold their food stock. To avoid this condition Government needs to make policy starting from monitoring, controlling, and sharing informationand open access of food commodity price. This research held on Lubuklinggau City, using literature study. All data collected from every source of references, research, and publications which tabulated and analized to redescripted. Based on this research conclude that indicator of food commodity price at Lubuklinggau City shows that the price is affordable, suitable with quality, competitive, and suitable with the benefit of the commodity. The development of agricultural commodity especially food commodity in Lubuklinggau City is wide open. The development of home industry is also potential and supported with the availablity of human resources and natural resources as a raw material of food industry. Keywords: food price, home industri, food security